Socio-psychological preconditions for the effectiveness of managerial decisions in business organizations - M. Y. Bikov; O. B. Repkina (Путеводитель предпринимателя)
The article examines the problems associated with the process of making managerial decisions in business organizations. Special attention is paid to the social and psychological aspects of the adoption of an effective managerial decision, the personality characteristics of the leader that influences this process; Some points have been singled out that the modern manager needs to take into account in his activity.